QOLP-20. DIETARY, ACTIVITY, AND QUALITY OF LIFE METRICS IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA IMPLEMENTING A KETOGENIC DIET: RESULTS OF A PHASE 1 CLINICAL TRIAL. (12th November 2021) - Nelson, Thomas; Gresham, Gillian; Welborn, Amelia; Amaral, L J; Noorvash, Brandon; Lockshon, Laura; Tighiouart, Mourad; Kim, Sungjin; Mack, Alexandra; Rudnick, Jeremy; Irwin, Scott; Freedland, Stephen; et al.
Abstract: BACKGROUND: Emerging evidence suggests that a ketogenic diet (KD) may limit neoplastic growth, but limited data exist regarding the effect of KD on daily activity, cognition, and health-related quality-of-life (HRQOL) for patients with glioblastoma. METHODS: Newly diagnosed GBM patients participating in a single-arm phase 1 trial of a 16-week KD plus standard-of-care measured BID blood glucose and ketone levels (Keto-Mojo), captured continuous activity data (Fitbit), and completed quality-of-life (QLQ30) surveys and Montreal Cognitive Assessments (MoCA) at baseline, Week 8, and study end (up to 16 weeks). NCT03451799. RESULTS: All patients (n = 14; 57% female; median age 55 years) maintained blood ketones above 0.3 mM > 50% of study duration (mean per-patient days in ketosis = 87%). Mean glucose (mg/dl) and ketone levels decreased through the study – Weeks 1/2: glucose 94.9 (SD:16.5), ketones 1.44 (SD:5.82); Weeks 3/4: glucose 94.1 (SD:12.9), ketones 1.34 (SD:0.9); Final two weeks: glucose 92.3 (SD:13.3), ketones 1.13 (SD:0.7). On average, patients walked 6, 836 steps/day (SD:5, 129), spending 14.3 hours sedentary (SD:6.45) and 43.6 minutes (SD:60.4) in high-intensity activity. Sleep duration was 6.8 hours (SD:2.26). Patients (n = 9) with OS > 14.6 mo from diagnosis demonstrated greater minutes of high-intensity activity (58.2 vs 20.7, p = 0.001), downtrending glucose (p = 0.001), and higher ketone levels (1.40 vs 1.11, p = 0.026). Activity data corroborated the tolerability of KD with stable-to-increased activity by study end. MoCA scores were stable from baseline (mean 23.4/30, SD:4.16) to study end (mean 24.8/30, SD:7.12; p = 0.38). When viewed as a composite score, HRQOL was stable-to-improving in 10/14 patients at Week 8 and EOS. CONCLUSION: The use of wearable technology and at-home testing allowed for remote monitoring of activity and diet adherence. Good adherence and stable HRQOL and activity levels were observed in this phase 1 trial.